2022
DOI: 10.3390/brainsci12030312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lexical-Semantic Cues during Real-Time Sentence Processing in Aphasia

Abstract: Using a visual world eye-tracking paradigm, we investigated the real-time auditory sentence processing of neurologically unimpaired listeners and individuals with aphasia. We examined whether lexical-semantic cues provided as adjectives of a target noun modulate the encoding and retrieval dynamics of a noun phrase during the processing of complex, non-canonical sentences. We hypothesized that the real-time processing pattern of sentences containing a semantically biased lexical cue (e.g., the venomous snake) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…To complement the growth curve analyses, we also conducted cluster-based permutation analyses to detect the temporal onset and duration of an effect between two time-series. This method was originally developed to account for the multiple comparison problem and autocorrelation arising in EEG and MEG data ( Maris & Oostenveld, 2007 ), and has been increasingly applied to eye-tracking research ( Akhavan et al, 2022 ; Baker & Love, 2021 ; Barr, Jackson, & Phillips, 2014 ; Gerhardstein & Olsen, 2020 ; Weighall, Henderson, Barr, Cairney, & Gaskell, 2017 ). In cluster-based permutation testing, inferential tests are performed on each time-bin over the analysis window and all adjacent, significant bins (i.e., passing a determined threshold) are grouped together into a single cluster and a cluster-level statistic is computed whose null distribution is derived through data permutation.…”
Section: Analysis Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…To complement the growth curve analyses, we also conducted cluster-based permutation analyses to detect the temporal onset and duration of an effect between two time-series. This method was originally developed to account for the multiple comparison problem and autocorrelation arising in EEG and MEG data ( Maris & Oostenveld, 2007 ), and has been increasingly applied to eye-tracking research ( Akhavan et al, 2022 ; Baker & Love, 2021 ; Barr, Jackson, & Phillips, 2014 ; Gerhardstein & Olsen, 2020 ; Weighall, Henderson, Barr, Cairney, & Gaskell, 2017 ). In cluster-based permutation testing, inferential tests are performed on each time-bin over the analysis window and all adjacent, significant bins (i.e., passing a determined threshold) are grouped together into a single cluster and a cluster-level statistic is computed whose null distribution is derived through data permutation.…”
Section: Analysis Approachmentioning
confidence: 99%
“…Experimental evidence has shown that in neurotypical adults and children (at least as young as 4 years of age), reactivation of the direct object occurs immediately at the gap position, resulting in the real-time formation of a syntactic dependency ( Akhavan, Blumenfeld, & Love, 2020 , 2022 ; Baker & Love, 2021 ; Koring, Mak, & Reuland, 2012 ; T. E. Love, 2007 ; Roberts, Marinis, Felser, & Clahsen, 2007 ; Thompson & Choy, 2009 , 2009 , p. 200). Although object-relative sentences are, in general, correctly comprehended by neurologically healthy adults, studies investigating real-time dependency linking have found that this process can be slowed or made more difficult in certain circumstances ( Gennari & MacDonald, 2008 ; Gibson, 1998 ; Gordon, Hendrick, & Johnson, 2001 , 2002 ; Traxler, Morris, & Seely, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations